The Basic Approach to the Evaluation of the Effectiveness of Treatment of Spasticity Syndrome in Children with Cerebral Palsy with Type A Botulinum Toxin Drugs - A. P. Solovyova; D. V. Goryachev; V. V. Arkhipov; N. D. Bunyatyan (Антибиотики и Химиотерапия, 2020)
The article covers basic scales and tests used in clinical trials and medical practice for the assessment of the effectiveness of treatment of spasticity syndrome with preparations of botulinum toxin type A in children with cerebral palsy. The article gives the information about the recommended methods of assessment, suggests the scales that can be used in evaluation of the effectiveness, as well as carries out an analysis of their informativity and sensitivity.